Deep learning with R for beginners : design neural network models in R 3.5 using TensorFlow, Keras, and MXNet /: design neural network models in R 3.5 using TensorFlow, Keras, and MXNet. (2019) - Hodnett, Mark; Wiley, Joshua F; Liu, Yuxi (Hayden); Maldonado, Pablo
No abstract available